A importância do processo administrativo e da cláusula do devido processo legal na administração pública brasileira contemporânea - Silva, Paloma Inayá Nicoleti da (2016)
The aim of this paper is to analyze the administrative process relevance and due process of law in the contemporary Brazilian public service, specially about the outlines provided by the Constitution of 1988. The analysis here described is divided into three chapters; Chapter I is intended as the study of due process of law historically developed and its ramification in relation to public service. Chapter II focuses on content of administrative due process of law, and at last, Chapter III is directed at administrative due process of law as an administrative action and support for validation. It is important to stress out that this paper has been based in laws and rules that regulate the subject, as well as the prevailing doctrinal understandings on the matter